Understanding potato with the help of genomics - Gálvez, J.H.; Tai, H.H.; Barkley, N.A.; Gardner, K.; Ellis, David; Stromvik, M.V. (American Institute of Mathematical Sciences, 2017)
Potato (Solanum tuberosum L.) is an important staple crop with a highly heterozygous and complex genome. Despite its cultural and economic significance, potato improvement efforts have been held back by the relative lack of genetic resources available to producers and breeders. The publication of the potato reference genome and advances in high-throughput sequencing technologies have led to the development of a wide range of genomic and transcriptomic resources. An overview these new tools, from the updated versions of the potato reference genome and transcriptome, to more recent gene expression, regulatory motif, re-sequencing and SNP genotyping analyses, paints a picture of modern potato research and how it will change our understanding of potato as well as other tuber producing Solanaceae.